Measuring the Contribution of Brand Image, Brand Trust, and Brand Loyalty to Sustainable Purchasing Behavior: A Case Study of The Body Shop in Malang - Didik Priyo Sugiharto (CV. Ulil Albab Corp, 2026)
This study aims to analyze the influence of Brand Image , Brand Trust , and Brand Loyalty on sustainable purchasing behavior among The Body Shop consumers in Malang. Using a quantitative approach with bootstrapping analysis in the Structural Equation Modeling (SEM) model , this study tested the direct relationship between variables based on primary data from 200 respondents. The results show that Brand Trust and Brand Loyalty have a significant and positive influence on sustainable purchasing, with path coefficients of 0.375 ( t-statistic = 3.462) and 0.445 ( t-statistic = 3.386), respectively, and a p-value = 0.000, indicating these two variables as the main drivers in the context of sustainable marketing . However, Brand Image does not show a significant direct influence, although it still plays a role as a foundation for forming initial perceptions. This finding confirms that the success of a sustainable marketing strategy depends not only on brand image, but more strongly on credibility and long-term emotional bonds with consumers. Thus, companies are encouraged to build transparency, consistency, and authentic customer experiences to strengthen trust and loyalty as the key to transforming attitudes into sustainable actions.